Konsep Manajemen Layanan Konsultasi untuk Mendukung Efektivitas Bimbingan dan Konseling di Sekolah - Habsy, Bakhrudin All; Indah, Nur Mutiara; Hutauruk, Andrea Briliana Christie; Febrianti, Aliya Putri (Lembaga Yasin AlSys, 2025)
Consultation services in guidance and counseling in schools are an important process in helping students, teachers, and parents to deal with various educational problems. This article aims to explore the concept of consultation service management by emphasizing a systematic and purposeful mechanism. Using a literature study approach, this research identifies the main stages in the implementation of consultation services, which include planning, organizing, implementing, and evaluating. The management model applied emphasizes collaboration between counselors, consultees, and third parties in dealing with student problems. The results of this study indicate that the application of good management concepts can increase the effectiveness of consultation services, create a conducive educational environment, and facilitate holistic problem solving. Thus, effective management is needed in the implementation of consultation services in order to have a positive impact on all parties involved.